A hydrothermal carbonization process for the preparation of activated carbons from hemp straw : an efficient electrode material for supercapacitor application - Jiang, Xia; Shi, Gaofeng; Wang, Guoying; Mishra, Puranjan; Liu, Chao; Dong, Yucan; Zhang, Peng; Tian, Haoqi; Liu, Yanrong; Wang, Zhao; Zhang, Qi; Zhang, Hongquan (Institute for Ionics, 2019)
In the present study, a hemp straw activated carbon (HSAC) was simply prepared by hydrothermal process followed by a pre-oxidization and carbonization by KOH solid-state activation. The as-synthesized HSAC shows abundant porosity, which is designed to be beneficial to the fast transportation of electrolyte. The preparation conditions for HSACs under different mass ratios of KOH:precursors were optimized, and the sample obtained by a mass ratio of 4:1 showed an outstanding capacitive property (specific capacitance of 279 F g−1at 0.5 A g−1 current density). Besides, the capacitance of 91.6% was retained after 5000 charge-discharge cycles under 2 A g−1 current density. The resulting symmetrical supercapacitor obtained by using the HSAC electrodes exhibited an excellent electrochemical performance, which successfully illuminated a LED light. The HSAC has great potentials as electrode material for high-performance supercapacitor, which opens a new way for value increment of natural products.